Intracytoplasmic sperm injection compared with in vitro fertilisation in patients with non-male factor infertility with low oocyte retrieval: a single-centre, retrospective cohort study - Liang Dong; Xin Liang; Shaomi Zhu; Hengli Li; Zili Lv; Dongmei Tian (BMJ Open)
Objective To investigate the effects of in vitro fertilisation (IVF) and intracytoplasmic sperm injection (ICSI) on the clinical outcomes of non-male factor patients aged >35 with three or fewer oocytes retrieved.Design Retrospective cohort study.Setting Reproductive centre of a university-affiliated hospital in China.Participants 547 women with non-male factor infertility who underwent assisted reproductive technology (ART) treatment with three or fewer oocytes retrieved were identified from June 2019 to May 2022. Of these 547 patients, 334 were treated with IVF and 213 with ICSI.Outcome measures The primary outcomes were normal fertilisation rate, live birth rate per transfer and cumulative live birth rate per retrieval.Results The baseline characteristics were comparable between the two groups, except for the proportion of primary infertility, which was higher in the ICSI group (17.66% vs 32.86%, p=0.000). Compared with the IVF group, the ICSI group showed higher normal fertilisation rate and lower cycle cancellation rate (65.99% vs 76.56%, p=0.002; 33.53% vs 24.41%, p=0.023). However, no significant differences were found in clinical pregnancy rate per transfer (23.86% vs 18.92%, p=0.545), miscarriage rate per fresh embryo transfer (19.05% vs 28.57%, p=0.595), live birth rate per transfer (17.05% vs 13.51%, p=0.623), cumulative clinical pregnancy rate per retrieval (12.87% vs 11.27%, p=0.576) and cumulative live birth rate per retrieval (9.28% vs 6.57%, p=0.261) between the two groups (p>0.05).Conclusions In non-male factor ART cycles, ICSI was not associated with improved pregnancy outcomes in older women with a low number of oocytes retrieved. Routine use of ICSI is not recommended in older women who are infertile due to non-male factors.